The effects muscle activities at constant illuminance with multiple temperatures for rubber scrap industries - Che Mohammad Nizam, Che Kamaruddin; Ahmad Rasdan, Ismail; Ong, Pit Wah; Ahmad Fauzi, Awang; Rosnizawati, Bharom (Excellent Publishers, 2015)
In the industrial sector, most workers perform repetitive loading and unloading tasks which majorly contribute to muscle fatigue to workers that affect their performance. The purpose of this study was to determine the effect of muscle activity associated with ergonomic parameters such as illuminance and temperature through the task of loading and unloading in the rubber industry in Malaysia. This study was conducted in the actual workplace and laboratory simulations involving the use of measuring temperature and illuminance. Meanwhile, a total of six respondents were selected and fitted with Electromyography (EMG) for muscle fatigue measurement on the right and left body side of employees. The data collected is analyzed to find out the correlation relationship within right body and left body. From the study, the dominant temperature 24°C is most suitable temperature level for the workers to perform their task while illuminance setting 200 lux has slightly effective on muscle fatigue.